Identification of neoantigen-reactive T lymphocytes in the peripheral blood of a patient with glioblastoma. Issue 7 (15th July 2021) - Leko, Vid; Cafri, Gal; Yossef, Rami; Paria, Biman; Hill, Victoria; Gurusamy, Devikala; Zheng, Zhili; Gartner, Jared J; Prickett, Todd D; Goff, Stephanie L; Robbins, Paul; Lu, Yong-Chen; et al.
Abstract : The adoptive transfer of naturally occurring T cells that recognize cancer neoantigens has led to durable tumor regressions in select patients with cancer. However, it remains unknown whether such T cells can be isolated from and used to treat patients with glioblastoma, a cancer that is refractory to currently available therapies. To answer this question, we stimulated patient blood-derived memory T cells in vitro using peptides and minigenes that represented point mutations unique to patients' tumors (ie, candidate neoantigens) and then tested their ability to specifically recognize these mutations. In a cohort of five patients with glioblastoma, we found that circulating CD4 + memory T cells from one patient recognized a cancer neoantigen harboring a mutation in the EED gene (EED H189N ) that was unique to that patient's tumor. This finding suggests that neoantigen-reactive T cells could indeed be isolated from patients with glioblastoma, thereby providing a rationale for further efforts to develop neoantigen-directed adoptive T cell therapy for this disease.